Arabic Usage in Indonesian Islamic Financial Contracts: Exploring Conceptual, Technological, and Socio-Cultural Integration - Desmadi Saharuddin; Hemmy Fauzan; Suhendra; Zulfikri Muhammad; Alaa Mustafa Abdelmaksud Abouagila (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
This comprehensive bibliometric and qualitative content analysis critically examines the evolving role of Arabic language contracts in Indonesian Islamic financial institutions, employing the Theory, Context, and Methodology (TCM) framework to integrate legal, cultural, and technological dimensions. The study strategically applies advanced science mapping protocols, with Scopus indexed extraction, rigorous contextual clustering, and descriptive relational text-mining approaches to synthesize 82 articles published between 2015 and 2025. The results highlight a persistent dominance of Shariah compliance, Arabic linguistic authority, and governance in contract legitimacy, yet they expose substantial gaps in public literacy, regulatory adaptation, and technological integration. Notably, empirical findings reveal that, despite regulatory intent, many stakeholders confront barriers to understanding and implementing Arabic contracts, with multilingual documentation and digital innovations like blockchain and fintech models offering solutions yet facing adoption challenges. The discussion situates these findings within broader research, demonstrating how they extend, nuance, and sometimes contradict prior studies through multidimensional analysis, particularly in local adaptation, stakeholder engagement, and the transformative impact of technology. Importantly, this review contributes novel theoretical and methodological perspectives, advocating composite models and advanced analytics to address persistent empirical gaps. Future research should prioritize comparative and longitudinal studies, innovative contract designs bridging language and technology, and big data methods to explore behavioral outcomes. Overall, this study establishes a foundation for more inclusive and resilient Islamic contract practice.